If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x^2+1)/(x+5)-x = 0;x
x
ln(1/e)
3*x^2-(11*x)-(5/(x^4))
50/(x^4)
3750*(1/5)
| (9x-6)+(-5x+7)= | | 1/18x=1/6 | | -y=4y-10 | | ((x^2/3)/4y^-2)^1/2 | | -1(-1-6)= | | (3xy^2-x^2)dx+(3x^2y-6y^2-1)dy=0 | | x-.45x= | | (x)(x)+11x-104=0 | | ln(x-10)+ln(x+10)=0 | | (x)(x)+11-104=0 | | 0.06+0.03(4000-x)=156 | | 5x+3.0=3x+3.3 | | 1/6-7/9= | | 9y^2-4= | | .7/42 | | 65x-11-4x=15+61x-26 | | 4x^2=19.188-63.69+53.3x^2 | | 7(2-m)=3n | | 9x+3y+(-6z)=18 | | y(x)=(18-0.5x)(5x+20) | | -28.5/-9.5x= | | x^2=0.000317-0.00072x-0.00041x^2 | | -30+1.5= | | 3(f-5)=6f-12+3f | | x^2=0.17784-1.8x | | -1.5/-1.2z= | | 40x^2-138x+119=0 | | -9.7+8.2= | | x^2=1.94994-6.21x | | 4x+2y+5x= | | 40x^2+80x-90=0 | | 27-8m=4m-3m |